The Skerin ridge on Eyjafjallajökull, south Iceland: Morphology and magma-ice interaction in an ice-confined silicic fissure eruption - Birgir Vilhelm Óskarsson 1982- (2010)
Skerin ridge is a 4.5 km long and on average 100 m wide ridge, situated on a radial fissure trending NW from the summit caldera of the ice-capped central volcano Eyjafjallajökull, south Iceland. Results from previous studies on tephrochronological dating of deposits produced by jokulhlaups originating in the Skerin area indicate that the ridge was formed by an intraglacial (or within glacier) eruption in the 10th century. Recent glacial recession has exposed the Skerin ridge and thus enabled a detailed examination of the ridge structure and architecture, in particular features that indicate confinement and rapid cooling by meltwaters as expected for lava-ice interaction. In this study, the ridge and associated formations were mapped in detail, the petrographic and chemical characteristics documented and the thickness of ice surrounding the ridge measured with a mobile radio-echo sounder. Skerin ridge is primarily constructed by trachytic lavas (volume ~0.043 km3) but also includes lesser mafic (basaltic icelandite/hawaiite) and intermediate (trachyandesite) tephra deposits (volume ~0.012 km3). Lithostratigraphy correlations indicate that the initial stage of the Skerin eruption was marked by a basaltic eruption creating a scoria cone on the NW end of the ice-free fissure with a phreatomagmatic eruption of same composition creating a tuff deposit on the SE ice-covered section of the fissure. At synchronous time an explosive eruption took place forming pumice deposits followed by an effusive eruption of trachyte lavas from a row of vents along the volcanic fissure. The lavas confined by wet cavities and canyons in the thin ice (~100 m) formed a marginal carapace of glassy columnar joints representing the area cooled by the meltwaters and a brecciated flow top being the subaerial expression of the flow as the lavas broke through the glacier. A massive microcrystalline flow interior with flow structures and fabrics formed within the crust typical for lavas cooled within an insulated environment. The eruption ended ...